Competency Development of Professional Librarians Based on the Standards in Determining the Position of Rajabhat Universities through the Process of Knowledge Management : - - Pimpasripirom, Prapaporn; Yeamsang, Tirawat; Worakul, Pornthip (Journal for Developing the Social and Community, 2021)
The purposes of the research were 1) to study the competencies and needs of librarians of Rajabhat universities for competency development, 2) to develop the competencies for professional librarians based on the standards in determining the position of Rajabhat Universities through the process of knowledge management, and 3) to assess the results of the competency development of the librarians of Rajabhat Universities participating in the competency development project. The population was 228 librarians from thirty eight Rajabhat University libraries. The research instrument was a questionnaire and an assessment form. The statistics used were percentage, arithmetic mean, standard deviation and Priority Needs Index (PNI). Results of the research were as follows: The research results showed that the overall competency of the professional librarians of Rajabhat universities was at a moderate level ( =2.99). The average knowledge of the librarians was at a moderate level ( =3.00). The three moderate rated items of overall skill of the professional librarians were personal qualities ( =3.01), knowledge ( =3.00) and skill ( =2.97) respectively. The findings showed that the overall need for competency development of the librarians was at a high level ( =4.02). The three high rated items of their need for competency development of the professional librarians were knowledge ( =4.03), skill ( =4.01) and personal qualities ( =4.00) respectively. The study showed that the workshop on professional competency development by using the guidelines of competency development was employed for twenty librarians of the northeastern Rajabhat University library network consisting of Office of Academic Resources and Information Technology of Rajabhat Buriram University, Rajabhat Si Sa Ket University, Rajabhat Udon Thani University, Rajabhat Nakhon Ratchasrima University and Rajabhat Maha Sarakham University. The workshop activities consisted of knowledge transfer, asking and answering questions, brainstorming and knowledge exchange and presentation and disseminating through the website of Office of Academic Resources and Information Technology Rajabhat Maha Sarakham University. The findings revealed that the overall satisfaction of the trainees with the three items of the workshop consisting of application of knowledge, contents, and location / time was at a high level ( = 4.04). The findings indicated that the average competency of the trainees after the workshop on the competency development for professional librarians regarding the satisfaction of members of the executive staff with the competency development of professional librarians of Rajabhat universities was at a high level ( = 4.24).